The Relationship of Leadership Style of the Head Room with Nurse's Work Motivation - Ika Maelany; Niken Sukesi; Chandar Hadi Prasetya (Indonesian Journal of Global Health Research, 2022)
Most of the hospital employees are nurses. Nurses work 24 hours to provide nursing care. Nursing with this large number of course requires reliable leadership. Leadership is one of the managerial aspects in organizational life that aims to influence, move and direct one's actions in certain situations to achieve goals. Leadership will be reflected in the leadership style that will be applied to subordinates. Leadership style is a form of behavior from a leader that can affect a person's work motivation and become a driving force for work morale. The purpose of this study was to analyze leadership with work motivation of nurses in hospital inpatient rooms. ype of research is a quantitative method with a non-experimental approach, with adesign cross sectional where data collection for the independent and dependent variables is carried out at the same time. The research sample consisted of 32 nurse with total sampling technique. The analytical test used is rank spearman. Results obtained are that the democratic leadership style affects the work motivation of high nurses with p value = 0.000 and Rho = 0.656